The effect of resistance training on hormones secreted from the adipose tissue (WISP-1 and WISP-2 ) in obese men - Sajjad Kermani; Asieh Abbassi Daloii; Ahmad Abdi; Ayoub Saeidi (فصلنامه ابن سینا)
Background and aims: A great importance has been given to the role of adipose tissue due to their ability to secrete hormones. The aim of this study was to evaluate the effects of resistance training (RT) on hormones secreted from adipose tissue (WISP-1 and WISP-2) in obese men. Methods: In the semi-experimental study, 44 obese men (32-33 years old) were selected and randomly divided into four groups of control, interval RT, traditional RT, and circuit RT. interval, traditional, and circuit RT were performed with intensity of 50% of maximum repetition and active rest, three sessions per week for 12 weeks. Serum WISP-1 and WISP-2 levels were measured using an ELISA kit. Data were analyzed by the correlated t-test, one-way analysis of variance, and Tukey‘s post-hoc test at the p<0.05. Results: The results showed that there was a significant difference among the effect of three training methods on WISP-1 in obese men (p<0.001), while there was no significant difference among the effect of three training methods on WISP-2. The level of WISP-1 in the interval RT group  was significantly lower than that in  the control and traditional RT groups. Also, WISP-1 in interval RT and circuit RT groups and WISP-2 in interval RT group decreased significantly compared to the pre-test (p<0.001). Conclusion: It seems that interval RT has more effects on reducing of WISP-1 and WISP-2 in obese men.